Septická sakroiliitida komplikovaná pseudoaneuryzmatem arteria iliaca interna - kazuistika - Salášek, M; Pavelka, T (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2016)
The case of a 67-year-old woman with a combination of pelvic pyomyositis and left-sided sacroiliitis is reported. After a failed two-week antibiotic therapy, CT-guided percutaneous drainage of psoas muscle abscesses was performed and methicillin-resistant Staphylococcus aureus (MRSA) was isolated. Subsequently, a regression of symptoms was observed. At 6.5 weeks after the onset of symptoms, progression of sacroiliac joint (SI) destruction was again observed and an open revision of the SI joint was indicated (posterior approach, drainage and lavage). This again was followed by symptom regression. At 9.5 weeks after the patient was admitted, her condition markedly deteriorated and a large gluteal abscess was detected on CT examination. The second revision surgery was complicated by massive bleeding and, due to a septic pseudoaneurysm, internal iliac artery ligation was necessary. A significant subsidence of inflammatory changes and no pseudoaneurysm were shown on the follow-up CT scan. The intravenous antibiotic therapy with clindamycin was continued. At follow-up, repeated microbiological cultures from both tissue samples and drained secretions were all negative and CT scanning detected neither any fluid around the SI joint nor a pseudoaneurysm.
Keywords: Ligation; Staphylococcal Infections; Staphylococcus aureus; arteria iliaca; Humans; lidé středního věku; sakroiliitida; Sacroiliac Joint; stafylokokové infekce; Female; ligace; Methicillin-Resistant Staphylococcus aureus; lidé; antibakteriální látky; nepravé aneurysma; methicilin rezistentní Staphylococcus aureus; ženské pohlaví; pyomyozitida; Anti-Bacterial Agents; Middle Aged; Sacroiliitis; Pyomyositis; absces psoatu; drenáž; Aneurysm, False; sakroiliakální kloub; Iliac Artery; Drainage; Psoas Abscess